Photocatalytic hollow TiO2 and ZnO nanospheres prepared by atomic layer deposition - Nóra Justh (Nature Portfolio, 2017)
Abstract Carbon nanospheres (CNSs) were prepared by hydrothermal synthesis, and coated with TiO2 and ZnO nanofilms by atomic layer deposition. Subsequently, through burning out the carbon core templates hollow metal oxide nanospheres were obtained. The substrates, the carbon-metal oxide composites and the hollow nanospheres were characterized with TG/DTA-MS, FTIR, Raman, XRD, SEM-EDX, TEM-SAED and their photocatalytic activity was also investigated. The results indicate that CNSs are not beneficial for photocatalysis, but the crystalline hollow metal oxide nanospheres have considerable photocatalytic activity.